PEMODELAN PERUBAHAN PENGGUNAAN LAHAN KABUPATEN HUMBANG HASUNDUTAN MENGGUNAKAN CLUE-S - Toga Pandapotan Sinurat; Khursatul Munibah; Dwi Putro Tejo Baskoro (Jurnal Ilmu Tanah dan Lingkungan, 2015)
The growth of a region has changed land-use pattern, not only in urban areas but also rural areas such as Humbang Hasundutan regency, North Sumatra Province. As one district that newly developed since its establishment in 2003, land-use change has affected the environment such as the emergence of degraded land due to deforestation and other environmental vulnerability issues in some sub districts. CLUE-S (the Conversion of Land Use and its Effects at Small region extents) model with a combination of dynamic systems and quantification of empirical relationships between land-use and its driving factors was chosen to predict land-use change that improves an understanding of land allocation planning. The aims of this study were to analyze land-use change in Humbang Hasundutan district and predict the changes in year 2033. The results showed Humbang Hasundutan district has 5,362 hectares of forest cover loss in period of years 2003 to 2013. Land use change simulation by using scenario with restricted area policy and forest land rehabilitation can maintain forest cover over 30 % and contribute to augment forest vegetation on degraded lands by 47.87 % in year 2033. Keywords: CLUE-S, degraded land, forest cover, land-use change